Double-Loaded Doxorubicin/Resveratrol Polymeric Micelles Providing Low Toxicity on Cardiac Cells and Enhanced Cytotoxicity on Lymphoma Cells - Lyubomira Radeva; Yordan Yordanov; Ivanka Spassova; Daniela Kovacheva; Virginia Tzankova; Krassimira Yoncheva (Pharmaceutics, 2023)
The anthracycline antibiotic doxorubicin is a well-known antitumour agent, however its cardiotoxicity is a significant obstacle to therapy. The aim of the present study was to improve the safety of doxorubicin through its simultaneous encapsulation with a cardioprotective agent (resveratrol) in Pluronic micelles. The formation and double-loading of the micelles was performed via the film hydration method. Infrared spectroscopy proved the successful incorporation of both drugs. X-ray diffraction analyses revealed that resveratrol was loaded in the core, whereas doxorubicin was included in the shell. The double-loaded micelles were characterised by a small diameter (26 nm) and narrow size distribution, which is beneficial for enhanced permeability and retention effects. The in vitro dissolution tests showed that the release of doxorubicin depended on the pH of the medium and was faster than that of resveratrol. In vitro studies on cardioblasts showed the opportunity to reduce the cytotoxicity of doxorubicin through the presence of resveratrol in double-loaded micelles. Higher cardioprotection was observed when the cells were treated with the double-loaded micelles compared with referent solutions with equal concentrations of both drugs. In parallel, treatments of L5178 lymphoma cells with the double-loaded micelles revealed that the cytotoxic effect of doxorubicin was enhanced. Thus, the study demonstrated that the simultaneous delivery of doxorubicin and resveratrol via the micellar system enabled the cytotoxicity of doxorubicin in lymphoma cells and lowered its cardiotoxicity in cardiac cells.